From a convergence to a reasoning with internal-valued probability - Diệu, Phan Đình; Quế, Trần Đình (Journal of Computer Science and Cybernetics, 2016)
Combining a deduction in a knowledge base of external uncertainty whose semantics has been proposed by N.J.Nilsson with a deduction coming from a convergence of a sequence of operators in a knowledge base of internal uncertainty, we propose a method of reasoning in a knowledge base of the both types of uncertainty. Let B an S be such a knowledge base and a goal sentence, respectively. The interval of truth probabilities of S derived from B can be found by the proposed method.